Fractalkine is not a major chemoattractant for the migration of neutrophils across microvascular endothelium - Beck, Grietje; Ludwig, F.; Schulte, Jutta; Ackern, Klaus van; Woude, Fokko J. van der; Yard, Benito A. (Scandinavian journal of immunology, 2003)
Inflammatory responses during sepsis are determined by leucocyte recruitment into inflamed tissues. Both chemokines and adhesion molecules are believed to be involved in this process. As fractalkine exists as transmembrane protein with cell adhesion properties and as soluble chemotactic factor, the present study was conducted to study the role of fractalkine, produced by microvascular and macrovascular endothelial cells, in neutrophil recruitment. Lung microvascular endothelial cells (LMVECs) stimulated with lipopolysaccharide, tumour necrosis factor-alpha or interleukin-1 (IL-1) produced much more fractalkine compared with the macrovascular human umbilical vein endothelial cells (HUVECs). No differences were found between microvascular endothelial cells of different organs. Chemotactic activity in supernatants was significantly stronger in stimulated LMVEC when compared with HUVEC. Although recombinant fractalkine induced migration of neutrophils, IL-8 and monocyte chemoattractant protein-1 were found to be more strictly required. In vivo fractalkine was strongly upregulated in septic lung and kidney. Our data suggest that fractalkine production per se does not explain the preference for inflammation in the lung of septic patients.
First published: 21 July 2003
Gesehen am 24.06.2022